PROCEDURAL UNFAIR WAGE DIFFERENTIALS AND THEIR EFFECTS ON UNETHICAL BEHAVIOR - Kerstin Grosch; Holger A. Rau (Economic Inquiry, 2020)
In this paper, we investigate how payment procedures that are deemed unfair can spur unethical behavior towards innocent coworkers in a real-effort experiment. In our Discrimination treatment, a highly unfair payment procedure with wage differentials, half the workforce is randomly selected and paid by relative performance whereas the remaining receives no payment. A joy-of-destruction game measures unethical behavior subsequently. Non-earners in Discrimination destroy significantly more than in the non-discriminatory control treatments. In Discrimination, unethical behavior is generally high for all non-earners, independent of individual inequality aversion and relative performance beliefs. In the control treatments, inequality aversion is the main driver of destructive behavior. (JEL C91, D03, J33, J70, M52)
Keywords: 330